Pengatuan Hukum Terhadap Narkotika Jenis-Jenis Baru yang Belum Terdaftar - Hakim, Rizky Maulana (Universitas Merdeka Madiun, 2020)
We realize that in the community, it is still close to the night world which can plunge the nation's next generation, through drinking, gambling, and especially Narcotics. There are many rules related to this problem, it is still possible that the minimum knowledge of the community is what causes users to become victims of the rigors of using drugs.In discussing this paper, we will take and discuss the theme of